Inhibition of plaque progression and promotion of plaque stability by glucagon-like peptide-1 receptor agonist: Serial in vivo findings from iMap-IVUS in Watanabe heritable hyperlipidemic rabbits - Sudo, Mitsumasa; Li, Yuxin; Hiro, Takafumi; Takayama, Tadateru; Mitsumata, Masako; Shiomi, Masashi; Sugitani, Masahiko; Matsumoto, Taro; Hao, Hiroyuki; Hirayama, Atsushi (Atherosclerosis, 2017)
Glucagon-like peptide-1 (GLP-1) is thought to inhibit development of aortic atherosclerosis and plaque formation. However, whether GLP-1 stabilizes fully developed atherosclerotic plaque or alters the complicated plaque composition remains unclarified. Ten Watanabe heritable hyperlipidemic (WHHL) rabbits were divided into GLP-1 receptor agonist treatment group and control group. After confirmation of atherosclerotic plaques in brachiocephalic arteries by iMap intravascular ultrasound (iMAP-IVUS), GLP-1 receptor agonist lixisenatide was administered to WHHL rabbits at 30 nmoL/kg/day for 12 weeks by osmotic pump. An equal volume of normal saline was administered in a control group. After evaluation by iMAP-IVUS at 12 weeks, brachiocephalic arteries were harvested for pathological histological analysis. iMAP-IVUS analysis revealed larger fibrotic plaque components and smaller necrotic and calcified plaque components in the GLP-1 group than in the control group; %fibrotic area: 66.30 ± 2.06% vs. 75.14 ± 2.62%, p < 0.01, %necrotic area: 23.25 ± 1.87% vs. 16.17 ± 2.27%, p = 0.02, %calcified area: 2.15 ± 0.24% vs. 1.00 ± 0.18%, p < 0.01), indicating that GLP-1 receptor agonist might modify plaque composition and increase plaque stability. Histological analysis confirmed that GLP-1 receptor agonist treatment improved smooth muscle cell (SMC)-rich plaque with increased fibrotic content. Furthermore, plaque macrophage infiltration and calcification were significantly reduced by GLP-1 receptor agonist treatment; %SMC area: 6.93 ± 0.31% vs. 8.14 ± 0.48%, p = 0.02; %macrophage area: 9.11 ± 0.80% vs. 6.19 ± 0.85%, p < 0.01; %fibrotic area: 54.75 ± 1.63% vs. 69.60 ± 2.12%, p = 0.02; %calcified area: 3.25 ± 0.67% vs. 0.75 ± 0.15%, p = 0.02). GLP-1 receptor agonist inhibited plaque progression and promoted plaque stabilization by inhibiting plaque growth and modifying plaque composition. •GLP-1 receptor agonist inhibited plaque progression.•GLP-1 receptor agonist promoted plaque stabilization by modifying plaque composition.•iMAP-IVUS was verified as a feasible and reliable tissue characterization system.